Encased Pultruded GFRP Beams with Shear Connectors: A Review - Allawi, Abbas A.; Ibrahim, Teghreed H.; Mahmood, Enas M.; Saadi, Tiba Hani; Khalaf, Mohammed Riyadh; Mohammed, Hussein K. (Engineering, Technology & Applied Science Research, 2025)
This study examines the structural performance of concrete-encased pultruded Glass Fiber Reinforced Polymer (GFRP) I-sections with shear connections. It specifically focuses on how different parameters affect the latter’s ductility, flexural strength, and load-carrying capacity. The key variables studied include various shear connector types, spacing, and geometries, as well as the compressive strength of concrete and the properties of GFRP. The finite element modeling and experimental validation show that the shear connectors significantly improve the ductility, ultimate capacity, and load transmission efficiency. The present review emphasizes that the shear connectors greatly enhance the structural performance when they are properly used. The long-term durability and failure modes must also be considered. For instance, having reduced the connector spacing from 375 mm to 100 mm increased the ultimate load by up to 34.5% in some cases, while having increased the concrete compressive strength from 30 MPa to 53.8 MPa led to a notable improvement in the flexural stiffness.